Influence of genetic and non-genetic factors on total female calves born and female calves reached milking herd in Phule Triveni crossbred cattle - SHINDE, KULADIP PRAKASH (Indian Journal of Dairy Science, 2017)
Present study was carried out on Phule Triveni crossbred cattle with the aim to determine the effect of genetic and non-genetic factors on total female calves born and female calves reached milking herd trait. Data on total female calves born and female calves reached milking herd traits in Phule Triveni crossbred cattle are maintained at Research-Cum-Development Project (RCDP) on cattle, Mahatma Phule Krishi Vidyapeeth Rahuri, Dist.- Ahmednagar (MS) over a period of 39 years (1976 to 2014) were analyzed in the study. The data was grouped into different sub-classes of season of calving, period of calving, age at first calving and genetic group of animals. In present study the average genetic variability for number of total female calves born, was 1.96Â±0.01 and period of birth, season of birth, age at first calving (AFC) and variation due to generation had non-significant effect on number of total female calves born but first lactation milk yield group had significant effect on total female calves born and random effect of sire also had shown significant influence on total female calves born trait. The average genetic variability for number of female calves reached milking herd, was 1.53Â±0.07 and period of birth, season of birth, age at first calving (AFC), variation due to generation, lactation milk yield and random effect of sire had non-significant effect on number of female calves reached milking herd. So, various environment factors significantly affected the total female calves born and female calves reached milking herd trait indicating the scope of improvement in management of these crossbred cattle.